Vesico-vaginal fistula as a complication of total laparoscopic hysterectomy: a case report and literature review - Sahu, Latika; Gandhi, Gauri; Singh, Shubhra (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Complications are possible in all type of surgeries including hysterectomy irrespective of the route of surgery, experience of the operating surgeon or the associated risk factors present. If the surgeon is careful from the beginning of the surgery and follows all the preventive measures complications like urinary tract injuries and vesico-vaginal fistula formation following hysterectomy can be avoided. Here we are presenting a case of vesico-vaginal fistula formed following total laparoscopic hysterectomy (TLH) and reviewed literature regarding incidence, preventive measures for this complication.